The Analysis of Renal Anatomy and Histological Changes of Green Iguana (Iguana Iguana) After Feeding With Red Spinach (Amaranthus tricolor L.) (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2019)
Background and Objective: Iguana breeders usually used red spinach as a feed for iguanas. However, several studies have indicated that red spinach contains oxalate and purine which are harmful if consumed at a certain level because they can interfere with kidney function. This study aimed to investigate the change of anatomy and histology of green iguana (Iguana iguana) kidney after feeding with red spinach. Materials and methods: Twelve iguanas were used in this study and were divided into four groups in accordance to the dose level of red spinach (100%, 75%, 50% and 25%, namely group I to IV, respectively). The red spinach was given for 30 days through the nasogastric intubation. The effect of red spinach administration was observed through the anatomy and histological changes. The results were statistically analyzed with One Way ANOVA with p
Keywords: Green iguana; Red spinach; Kidney; Anatomy change; Histology change